Investigating the results of neuroendoscopic surgery in the treatment of pituitary adenoma and leptin gene expression: Neuroendoscopic Surgery and Pituitary Adenoma - Zhang, Pengbo; Ren, Dengpeng (Cellular and Molecular Biology, 2022)
Neuroendoscopic surgery of pituitary adenoma has been one of the technologies with rapid progress in neurosurgery in this decade. This method has known advantages and limitations. This study aims to investigate the results of pituitary adenoma treatment using the neuroendoscopy technique in a group of patients. Also, the level of leptin gene expression (LEP), which is produced exclusively in the pituitary gland, was measured for further evaluation. For this purpose, 26 patients who were diagnosed with pituitary adenoma and underwent endoscopic surgery in the hospital between 2018-2022, in terms of age, gender, disease symptoms, functional and non-functional tumor, and neurological examination findings before and after the procedure, complications, and the length of stay in the hospital were investigated. Also, before and 6 months after the operation, blood samples were prepared from patients to evaluate LEP gene expression by real-time PCR technique. The results illustrated that of the 26 patients studied, 14 were men, and 12 were women. Most of the patients were in their third to sixth decades of life. The tumors were non-functioning adenoma in 11 cases, somatotroph adenoma in 9 patients, corticotroph adenoma in 3 cases, and prolactinoma in 3 cases. Seven patients suffered postoperative complications, including 6 cases of reversible complications and one case of patient death. In the 2-year follow-up, 6 cases of tumor recurrence were observed. Also, the evaluation of LEP gene expression showed no significant difference between pre-operative and post-operative expressions. In general, neuroendoscopic surgery in treating pituitary adenoma is a method worthy of attention, considering factors such as fewer complications and a shorter stay in the hospital increase the acceptability of this method.